Three Early Experiments in Multicursal Storytelling in Animated Films - Margaritis, Charalambos (My University, 2023)
This paper discusses an ongoing practice-based research focusing on the application of modular and multicursal narrative structures in animated film. The goal is to create animated films whose structure and order of unfolding changes dynamically, resulting in nonlinear, yet coherent, narrative discourses. This modularity is applied on all levels of narrative components of the film: scenes, shots and individual frames. These alternative narrative structures are made possible by digital technologies and have been developed primarily in the framework of interactive media – such as video games or digital hypertexts. Therefore, in order to apply them to a visual storytelling medium such as the animated film, a set of software has been developed for the purposes of this research (and will further be developed as the research advances). These software function as modulable, dynamic and multicursal systems of arranging the animated film’s narrative parts (scenes, shots and individual frames) in various orders while presenting them - while the film is playing. An important parameter to keep in mind is that the research seeks to differentiate the proposed systems from interactive media and avoid interactivity, since the end result at which the research aims is to produce films that are experienced by spectators, not users. Therefore, the software produced in this framework will have to evolve, unfold and be presented altogether in a way to preserve the dimension of spectatorship which is inherent and central to the filmic experience. The intention is that, by the completion of this research, a series of films will be created whose presentation will be possible through the use of these software. These films are destined to be presented in a screening context, such as all “regular” films are; but they will also be able to be presented as artworks in an exhibitional context (either as video installations or as simple screenings in space-specific contexts). This paper presents a very brief overview of the theoretical framework of this research, and proceeds by discussing three very early test experiments that demonstrate the practical implications of this proposition.
Keywords: animation; storytelling; narrative; nonlinear